Meningkatkan Kemampuan Sosial Emosional Anak Usia 5-6 Tahun Melalui Permainan Tradisional Engklek di PAUD Kober Nurul Hikmah Kabupaten Cianjur - Suryani, Yuli (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
Playing is an activity carried out anywhere, using materials or tools that can develop children's talents or imagination. Social emotional development is a child's sensitivity to understanding other people's feelings when interacting in everyday life. The level of a child's interaction with other people starts from parents, siblings, playmates to the wider community. One game that can be used to improve the social emotional skills of children aged 5-6 years is the traditional game of engklek. In this research, the researcher aims to find out how much influence the traditional game of engklek has on children's social emotional abilities at PAUD Nurul Cianjur. This research was carried out based on the findings of children who had not yet appeared. This research used the Classroom Action Research method, with subjects as many as 15 children from PAUD Nurul. The cycle used in implementing activities is 2 cycles. Implementation activities refer to daily learning plans that have been prepared and adapted to the needs of the research theme.